Primary central nervous system lymphoma post kidney transplantation: a case report - Khemiri, Souhir; Masmoudi, Sonda; Kridis, Wala Ben; Khanfir, Afef (Journal of Clinical Nephrology, 2022)
Introduction: Primary central nervous system (PCNS) posttransplant lymphoproliferative disease (PTLD) is a rare complication of solid organ transplantation and treatment is not yet standardized. Case presentation: Here we report the case of a 54-year-old man who underwent renal transplantation 22 years ago for end-stage renal disease. He had been on long-term immunosuppressive treatment consisting of orally administered prednisolone 10 mg and then 5 mg daily and orally administered Mycophenolate Mofetil 500 mg twice daily. He presented in January 2019 to emergency with aphasia and then partial seizure. On brain MRI there was an expansive cortical mass in the left temporal lobe with perilesional edema. Biopsy revealed a diffuse large B-cell lymphoma. He was treated with one cycle of Cytarabine with his usual immunosuppressive treatment. In view of his renal allograft, he was not suitable for Methotrexate due to the risk of toxicity. He died on day 15 caused by a sepsis choc secondary to febrile neutropenia. Conclusion: PCNS-PTLD is regarded as one of the most serious posttransplant complications due to its high mortality. Further clinical and experimental investigations are required to develop optimal diagnostic and treatment modalities.